Students Satisfaction with Their Body Images and Their Attitudes Toward Plastic Surgery - Muhammad, Zahid Sami; Arezi, Musaab Abdulhafidh Zainal (STAI Publisistik Thawalib Jakarta, 2025)
TBody image dissatisfaction and increasing interest in cosmetic procedures present significant psychosocial challenges among contemporary university students. This study examined body image satisfaction levels, areas of physical dissatisfaction, and attitudes toward plastic surgery among University of Zakho students. A descriptive survey approach collected data from 49 students (28 males, 21 females) using a validated 10-item questionnaire measuring satisfaction and attitudes. Analysis revealed hierarchical patterns of body dissatisfaction, with the nose being most dissatisfying facial feature (91.8% reported some facial dissatisfaction), followed by hair. The chest area generated highest body dissatisfaction (80% of those reporting body issues), followed by abdomen/buttocks. Students strongly perceived increased prevalence of cosmetic procedures (67.3% agreed